2017
DOI: 10.1007/s00428-017-2262-4
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic non-small cell lung carcinoma a mimic of primary breast carcinoma—case series and literature review

Abstract: Metastatic tumors to the breast are rare but constitute a major diagnostic dilemma. Of these, non-mammary carcinomatous metastases to the breast are particularly challenging and, without a clinical history, may be extremely difficult to distinguish from primary breast carcinoma (PBC). We specifically studied metastatic tumors of pulmonary origin, as the lung is one of the major primary sites for carcinomatous metastasis to breast. Sixteen metastatic lung tumors to the breast were identified in our archives bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 44 publications
0
18
0
1
Order By: Relevance
“…Alva and Shetty Alva (12) reported 78 cases in their literature review from 1855 to 1998. The most recent and largest review published in 2018 has reported 169 cases from 1999 to 2017 (13). In the cases of Alva and Shetty Alva (12), we have found 180 additional cases of metastatic lung tumors in the breast and made a summary of a total of 258 cases published in English until 2019.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Alva and Shetty Alva (12) reported 78 cases in their literature review from 1855 to 1998. The most recent and largest review published in 2018 has reported 169 cases from 1999 to 2017 (13). In the cases of Alva and Shetty Alva (12), we have found 180 additional cases of metastatic lung tumors in the breast and made a summary of a total of 258 cases published in English until 2019.…”
Section: Discussionmentioning
confidence: 98%
“…Lung cancer, which is a common malignancy and one of the leading cancer-related causes of death worldwide, frequently spreads to other organs but metastasizes to the breast very rarely. A few reviews have previously been published on lung cancer metastasizing to the breast (3,4,(10)(11)(12)(13). Alva and Shetty Alva (12) reported 78 cases in their literature review from 1855 to 1998.…”
Section: Discussionmentioning
confidence: 99%
“…29 Biomarkers of TTF-1 for lung cancer, CDX2 for gastric cancer, CD56(+), Syn, CgA for neuroendocrine cancer and WT-1 and CA125 for ovarian cancer are common markers for identification of the origin of metastatic lesions. 3,9,22,30 TTF-1 is expressed in most lung adenocarcinomas and small cell carcinomas accounting for 70-80%, and usually most cells are positive. 25,31,32 TTF-1 is rarely expressed in other types of lung cancers.…”
Section: Dovepressmentioning
confidence: 99%
“…2,[4][5][6] Breast metastases have also been reported in primary cancers such as melanoma, lung cancer, ovarian cancer, gastric cancer and neuroendocrine cancer. [7][8][9] To avoid unnecessary and potentially harmful treatments, accurate diagnosis of secondary breast carcinoma is very important. Identification of the primary and secondary breast tumors is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…According to sporadic case reports, the breast was reported as a metastatic site for primary lung adenocarcinomas and the incidence of breast metastases from an extramammary primary tumor can be as low as 0.5-3.0% (2)(3)(4)(5)(6)(7). Because of its rarity, even with known history of lung cancer, breast metastases would have been easily misdiagnosed as primary breast cancer and thus leads to unnecessary mastectomies (6,8,9). Due to the distinct biological mechanisms, advanced lung adenocarcinoma and breast cancer are treated with different therapies, such as EGFR tyrosine kinase inhibitors (TKIs) for lung cancer, and estrogen receptor (ER), progesterone receptor (PR) related endocrine treatment or human epidermal growth factor receptor 2 (HER-2) related target therapy for breast cancer.…”
Section: Introductionmentioning
confidence: 99%